2016
DOI: 10.1080/10837450.2016.1221427
|View full text |Cite
|
Sign up to set email alerts
|

In vitro aerodynamic characteristics of aerosol delivered from different inhalation methods in mechanical ventilation

Abstract: Aerodynamic characteristics of aerosol delivery during invasive mechanical ventilation (IMV) are mostly determined by inserting cascade impactor in the circuit. Impactor might have some effect on airflow within IMV. Hence, the aim of the present study was to develop and evaluate new in vitro aerodynamic characterization methodology without affecting airflow in IMV. Breathing simulator was set in standard adult IMV circuit with inspiratory and expiratory pressures of 20 and 5 cm HO, 1:3 inspiratory-expiratory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…VMNs again showed much better efficiency in aerosol delivery compared to JN, resulting in higher inhaled dose (p\0.001) and lower residual dose (p\0.001) [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…VMNs again showed much better efficiency in aerosol delivery compared to JN, resulting in higher inhaled dose (p\0.001) and lower residual dose (p\0.001) [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Salbutamol entrained on the filter was described as total inhaled dose (aerosol emitted) and assayed for salbutamol using previously validated highperformance liquid chromatography. 12,13,25,26,32,33 We used the 25 mm ϫ 4.6 mm Zorbax Eclipse Plus C18 and the ODS1 column (Agilant), through which the mobile phase consisted of a mixture of acetonitrile and water (0.1% phosphoric acid) (90:10, v/v) was pumped at 1 mL/min using the 1260 Infinity preparative pump (G1361A, Agilant) the 1260 Infinity Diode array detector VL (G131SD, Agilant) was set at 225 nm with an injection volume 100 L. Calibration solutions ranged from 4 to 100 g/mL (weight/volume). Limit of detection was 0.35 g/mL, and the lower limit of quantification was 2.55 g/mL.…”
Section: Ex Vivo Methodsmentioning
confidence: 99%
“…[4][5][6][7] The type and position of the aerosol generator, ventilator settings during aerosol delivery, and other variables during NIV have been investigated. 4,5,[7][8][9][10][11][12][13][14][15][16][17][18] Many previously published studies recommended switching off the humidifier while delivering aerosol for improved aerosol delivery. 9,19,20 However, we have shown that there was no significant effect on delivered aerosol associated with this practice during auto-CPAP or duallimb ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the patient interface (mask vs endotracheal tube) and placement of the aerosol generator differ with noninvasive ventilation (NIV) compared with conventional invasive ventilation. [10][11][12][13] In a previous in vitro study, we reported that the standard T-piece and large spacer were equally efficient for salbutamol delivery by a vibrating mesh nebulizer in a single-limb NIV under nonhumidified conditions. 14 In vitro methods that study the aerodynamic characteristics and fate of aerosol by using a lung simulator model are thought to offer some degree of guidance to clinical delivery and response.…”
Section: Introductionmentioning
confidence: 93%